IVC treatment between primary and second TURBT may improve the prognosis of high-risk NMIBC patients receiving BCG treatment - Zhen Li; Zewei Wang; Yang Liu; Lei Yang; Ling Gu; Hailong Li; Wei Wang (Scientific Reports, 2025)
Abstract To explore whether intravesical chemotherapy (IVC) between primary and second transurethral resection of bladder tumor (TURBT) affects the prognosis of non-muscle invasive bladder cancer (NMIBC) patients receiving Bacillus Calmette-Guérin (BCG) treatment. NMIBC patients who underwent a second TURBT and subsequent BCG treatment between 2012 and 2023 at the Affiliated Hospital of Xuzhou Medical University were retrospectively analyzed. These patients were divided into Group A, which received IVC between TURBT, and Group B, which did not. Recurrence-free survival (RFS) was compared among the different risk subgroups. A total of 292 NMIBC patients were included in this study. In the entire cohort, IVC treatment between the primary and second TURBT was associated with longer RFS (P = 0.009). When stratified by risk groups, in intermediate-risk patients, the difference in RFS between the groups was not statistically significant (P = 0.434). By contrast, for high-risk patients, the treated group exhibited a better prognosis compared to the non-treated group (85.6% vs. 77.6%, P = 0.007). In both univariate and multivariate COX regression analyses, after adjusting for clinical factors such as tumor stage and tumor grade, the IVC between the primary and second TURBT remained an independent prognostic factor for NMIBC patients (HR 0.571, 95% CI [0.380, 0.859], p = 0.007). IVC treatment administered between the primary and second TURBT has been demonstrated to enhance RFS of high-risk NMIBC patients undergoing BCG treatment, whereas it is not applicable to intermediate-risk patients.